PENGGUNAAN MEDIA ONLINE DALAM PROSES PEMBELAJARAN PAI PADA WAKTU PANDEMI COVID-19 - Yasin Muhammad Syibli (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
Learning problems in schools still require improvement both technically, learning methods, media and those related to the learning process in schools, when the world is faced with a pandemic that hits. Where the epidemic has an impact on learning in schools. This situation forces the world of education to carry out the learning process online. The purpose of writing this article is to study and understand the use of online media in learning Islamic Religious Education (PAI) during the Pandemic. Writing this article using a qualitative approach with secondary data sources obtained from online observations and literature reviews. The results of the research prove that the use of online media during this pandemic has caused various responses and impacts and changes in the learning system that can affect the learning process and the level of student development in responding to the material presented